Development of Interactive Learning Media Based on Website Using Google Sites at SMK Negeri 1 Samarinda - Muhammad Fatwa Putera Adrian; Galih Yudha Saputra (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The rapid advancement of information technology requires the education sector to adapt by adopting modern learning methodologies. SMK Negeri 1 Samarinda, a leading vocational institution, faces challenges in providing engaging learning materials, especially in the Computer Network Engineering (TJKT) department. Observations show that conventional media, such as PowerPoint presentations, printed modules, and WhatsApp groups, are often monotonous, reducing student motivation. This research aims to develop interactive website-based learning media using Google Sites for the Basic Vocational Program subject. The study employed the Planning, Production, and Evaluation (PPE) development model. Data were collected through observations and questionnaires, analyzed using descriptive methods. The developed media was evaluated by one content expert, three media specialists, and tested with 28 students from Class X TJKT. Results indicate that the media received an average score of 4.6 from content experts (highly feasible), 4.4 from media experts (highly feasible), and an 84.56% positive response from students. The website includes instructional materials, educational videos, interactive games, assessment tools, and feedback mechanisms, accessible on any internet-connected device. This web-based platform enhances student engagement through multimedia integration and offers flexible resource access, serving as an effective solution to limited educational infrastructure. The implementation addresses technological constraints while preparing students for the digital workplace they will encounter in their future careers.